Improving the relevance and consistency of outcomes in comparative effectiveness research. (March 2016) - Tunis, Sean R; Clarke, Mike; Gorst, Sarah L; Gargon, Elizabeth; Blazeby, Jane M; Altman, Douglas G; Williamson, Paula R
Policy makers have clearly indicated – through heavy investment in the Patient Centered Outcomes Research Institute – that reporting outcomes that are meaningful to patients is crucial for improvement in healthcare delivery and cost reduction. Better interpretation and generalizability of clinical research results that incorporate patient-centered outcomes research can be achieved by accelerating the development and uptake of core outcome sets (COS). COS provide a standardized minimum set of the outcomes that should be measured and reported in all clinical trials of a specific condition. The level of activity around COS has increased significantly over the past decade, with substantial progress in several clinical domains. However, there are many important clinical conditions for which high-quality COS have not been developed and there are limited resources and capacity with which to develop them. We believe that meaningful progress toward the goals behind the significant investments in patient-centered outcomes research and comparative effectiveness research will depend on a serious effort to address these issues.